Contribution of Completeness of Learning Media to Students' Islamic Religious Education Learning Outcomes at SMP Negeri 2 Padangsidimpuan, Indonesia - Nasution, Afridah; Annisa Hilda PANJAITAN; Syafnan (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study aims to analyze the contribution of the completeness of learning media to the learning outcomes of Islamic Religious Education (PAI) of students at SMP Negeri 2 Padangsidimpuan, Indonesia. The method used in this study is a quantitative approach with descriptive and correlational designs. The study population consisted of all students of grade VIII, with a sample taken by purposive sampling of 60 students. Data were collected through questionnaires to measure the completeness of learning media and PAI learning outcome tests to measure students' academic achievement. The results of the analysis showed that there was a significant positive relationship between the completeness of learning media and students' PAI learning outcomes. The average learning outcome score of students who used complete learning media was higher than that of students who used incomplete learning media. This finding indicates that the use of varied and complete learning media can improve students' understanding and learning outcomes in PAI subjects. This study suggests that PAI teachers at SMP Negeri 2 Padangsidimpuan make better use of and complete existing learning media to improve learning effectiveness. In addition, school administrators are expected to provide adequate resources to support the use of better learning media.